Programmed cell removal by calreticulin in tissue homeostasis and cancer - Mingye Feng (Nature Portfolio, 2018)
Macrophage-mediated programmed cell removal (PrCR) allows clearance of living cells. Here the authors show that, in mouse models, activated macrophages create an “eat me” signal via calreticulin secretion on neutrophils during peritonitis and on cancer cells, determining in both cases clearance by PrCR.